Authority of the Public Order Enforcers in Organizing Public Order in Badung Regency - I Gede Suanda Dwija (Jurnal Hukum Prasada, 2019)
This research is based on the background of the problem of the gap between the substance of the Regional Regulation of Badung Regency Number 7 of 2016 concerning Public Order and Peace of the People in the Badung Regency region with the facts that occur in the field. The aims was to find out how the authority and remedies for enforcement of regional government regulations in the context of implementing public order and peace of mind by the Public Order Enforcersin Badung Regency. The research method used is quantitative descriptive with an empirical legal research approach. The data used are primary data, secondary data and tertiary data. The method of determining the sample used is probability sampling. Data is collected through documentation techniques, observation and interviews. The results showed that the authority of Badung District Public Order Enforcersin organizing public order was regulated in the Badung District Regulation Number 7 of 2016 and supported by other Regulations in the Badung Regency area. Legal efforts of the Public Order Enforcers such as the act of controlling, demolition, sealing, closing the business operations and so forth. The remedies are pre-incentive non-judicial and judicial.